(untitled) (Journal of Management and Social Sciences, 2020)
Online Public Access Catalogue gained traction in the developed world decades ago, while its adoption has gradually peaked in developing countries, Nigeria inclusive. Just four years ago, the facility was installed at Fountain University Nigeria. Literature over time has shown that the availability of OPAC does not necessarily translate to use, hence this paper seeks to evaluate the level of usage of OPAC by students of Fountain University to contribute to ongoing discussions on better appreciation, effective implementation as well as the productive application of OPAC in libraries. The study adopted quantitative methods using a survey. Total sampling was employed using the entire nine hundred and eighty-two students as the sample size to give equal representation to all the departments and courses in the university, most importantly those that have few students. A questionnaire consisting of a set of close and open questions was designed as a research instrument to elicit data from the respondents. Five hundred and ninety (590) respondents returned the questionnaire which was further collated for further interpretation and analysis based on descriptive statistics, such as frequency counts and percentages. The findings show a general awareness of the existence of OPAC devoid of deep appreciation of its essence and operations among other challenges. There is therefore a pressing need to widen the scope of user education and orientation classes to include all the intricacies. Keywords Fountain University Library, OPAC utilization, user interface, student-clients